PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) AKIBAT PENGGUNAAN KOMPOS KULIT GELONDONG KOPI DAN PUPUK SS - Khadijah, Khadijah; Hairunnas, Hairunnas; Syifa, Aina (Cangkok, 2023)
This research aims to determine the effect of growth and yield of Pakcoy plants and to determine the effect of interaction between these two factors. This research was carried out in Bandar Lampahan Village, Gajah Putih District, Bener Meriah Regency with an altitude of 1272 above sea level with a pH of 7. The parameters observed consisted of from Plant Height at 7, 14 and 21 days after planting, Number of Leaves at 7, 14 and 21 days after planting, Weight Per Plant at 25 days after planting, and stover weight per plot at 25 days after planting. The results of the research showed that the use of coffee spindle shell compost and SS fertilizer had a very significant effect on the weight per plant at 25 days after planting and the weight of stover per plot at 25 days after planting. There was a very real interaction between Coffee Spindle Compost and SS Fertilizer when observing the Weight Per Plant at 25 days after planting.